Blasphemy of Salman Rushdie and shifting legal discourse in India - Rashid, Misbah (Contemporary Islam, 2020)
The domain of religion is thought to be rapidly losing significance in the age of secularization. But in contemporaneity, pertinent is the fact that religion has not been wiped away completely or even become any less significant. The religious laws are constantly under process of revision to be in consonant to social and political change. The case of Salman Rushdie in this regard is very well known. He was accused of blasphemy and a fatwa of death was pronounced against him from Iran. This article attempts to evaluate the reasons as to why this fatwa which is just a legal opinion became so important and generated reactions from every part of the world irrespective of sectarian divides in Islam. It also analyses the opinions of the two Islamic schools of thought in the Indian subcontinent – Deoband and Barelvi on the issue of blasphemy and the negotiations they make within their legal discourses to arrive at conclusions with regard the conflictual Islamic and secular laws. Despite emanating from the same Islamic school of jurisprudence – Hanafi but still varying in important aspects of religion, they adopt divergence with regard to the issue of blasphemy.